Severe Acute Biliary Pancreatitis: Mininvasive Approach - De Biasio, Pasquale; Gorgoglione, Maria Concetta; Fersini, Alberto; Tartaglia, Nicola; Ambrosi, Antonio; Neri, Vincenzo (JOP. Journal of the Pancreas, 2012)
Context Severe acute biliary pancreatitis is about 20% of all the pancreatitis. The relapse of the untreated cases is >20%. Objective The aim of the study is to define a mininvasive approach of the SABP: the maintenance of papillary patency and the treatment of the peripancreatic fluid gatherings and of the gallstones. Patients and Methods In the period 1999-2011, 60 severe acute biliary pancreatitis were treated: 42 necrotizing cases and 18 cases with pancreatic edema. All patients underwent ERCP/ES within 72 hours; it was successfully executed in 50 cases, in 7 cases it was delayed of 10 days, and it was non practicable in 3 cases. CT-scan guided percutaneous drainage was used for 3 infected peripancreatic and 2 intrahepatic gathering; another 2 infected gatherings were drained by laparotomic access. Cholecystectomy within 30 days: laparoscopic in 56 patients (93%). Results There were 4 post-ERCP pancreatitis (6.6%), failure of the procedure in 3 cases (5%) and no cholangitis, hemorrages or duodenal perforations; no morbidity for cholecystectomy neither for percutaneous drainage with resolution within 10 days. One patient (1.6%) died in 20th day because of DIC. Conclusions The mininvasive approach of the severe acute biliary pancreatitis is an efficacious and safe therapeutic program with a long period of resolution (mean 35 days) but satisfying for the results.